Prognostic value of electrocardiographic abnormalities in adults from the Brazilian longitudinal study of adults' health. Issue 19 (23rd December 2020) - Pinto-Filho, Marcelo Martins; Brant, Luisa Caldeira; dos Reis, Rodrigo Padilha; Giatti, Luana; Duncan, Bruce Bartholow; Lotufo, Paulo A; da Fonseca, Maria de Jesus M; Mill, Jose Geraldo; de Almeida, Maria da Conceição Chagas; MacFarlane, Peter; Barreto, Sandhi Maria; Ribeiro, Antonio Luiz Pinho
Abstract : Objective: Cardiovascular diseases (CVDs) are highly preventable non-communicable diseases. ECG is a potential tool for risk stratification with respect to CVD. Our aim was to evaluate ECG's role in all-cause and cardiovascular mortality prediction. Methods: Participants from the Brazilian Longitudinal Study of Adult Health, free of known CVD at baseline were included. A 12-lead ECG was obtained at baseline (2008–2010). Participants were followed up to 2018 by annual interviews. Deaths were independently reviewed. Cox as well as Fine and Grey multivariable regression models were applied to evaluate if the presence of any major electrocardiographic abnormality (MEA), defined according to the Minnesota Code system, would predict total and cardiovascular deaths. We also evaluated the Net Reclassification Index of adding MEA to the Systematic Coronary Risk Evaluation (SCORE). Results: The 13 428 participants (median age 51 years, 45% men) were followed up for 8±1 years. All-cause and cardiovascular mortality occurred in 2.8% and 1.2% of the population, respectively. Prevalent MEA was an independent predictor of overall (HR=2.3, 95% CI 1.7 to 2.9) and cardiovascular mortality (HR=4.6, 95% CI 3.0 to 7.0) after adjustments for age, race, education and traditional cardiovascular risk factors. Adding MEA to the SCORE resulted in 9% mis-reclassification in the non-event subgroup and 33% correct reclassification in those with a fatal cardiovascular event. Conclusion: Presence of MEA was an independent predictor of overall and cardiovascular mortality. ECG may have a role in risk prediction of cardiovascular mortality in primary care.